Buccal-lingual localization of the mandibular canal in relationship with the third molar using the lateral oblique technique - Gainer Raul Jasa; Mariana Boessio Vizzotto; Priscila Fernanda da Silveira; Heloisa Emilia Dias da Silveira; Heraldo Luis Dias da Silveira; Leticia Ruhland Correa; Tabare Raveca (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to evaluate the use of lateral oblique radiography (LOR) at two different incidence angles for the bucco-lingual topographic localization of the mandibular canal with respect to the lower third molars. Materials And Method: A total of 24 dry jaws bearing at least one third molar were subject to LOR at vertical incidence angles of 0° and -30°. A trained and calibrated examiner measured the distance between the top of the mandibular canal to the most apical point of the third molar, using a digital calliper and individual light box for the radiographs. Based on the analysis of the two measurements (incidence angles of 0° and -30°) and considering the buccal object rule, the observer estimated the location of the mandibular canal, which was classified as lingual, central or buccal to the corresponding third molar. Results were compared with the computerized tomography images (gold standard). Results: The statistical analysis included sensitivity, specificity and accuracy tests. These results showed that LOR (0° e -30°) could be used to determine the bucco-lingual location of the mandibular canal with respect to the third molar. Conclusion: In spite of the magnification, LOR images demonstrated that the technique could be used for this study proposal.